Perbandingan efisiensi algoritma linear search dengan algoritma binary search - Zamroni, Ahmad Zamroni (Maliki Interdisciplinary Journal, 2025)
Linear search and binary search are two commonly used algorithms in data processing. Linear search is known for its simplicity and ability to work with unsorted datasets, while binary search is more efficient for large, sorted datasets. This study compares the efficiency of both algorithms based on time complexity, space complexity, data conditions, and dataset size. The analysis results show that linear search is more suitable for small datasets or unsorted data, whereas binary search is significantly more efficient for large, sorted datasets. By understanding the characteristics of each algorithm, users can choose the most appropriate one for their specific needs.